Retention Rate of Free Pericardial Fat Grafts after Bronchial Stump Coverage - Karasaki, Takahiro; Fujimori, Sakashi; Suzuki, Souichiro; Kikunaga, Shinichiro (The Thoracic and Cardiovascular Surgeon, 2024)
The postoperative course of the graft tissue after bronchial stump coverage remains unclear. We retrospectively analyzed 44 patients who underwent anatomical lung resection followed by bronchial stump coverage using free pericardial fat grafts. All patients underwent minimally invasive video-assisted thoracoscopic surgery. Computed tomography scans showed a graft retention rate of 100% on 60 days after surgery, 61% on 180 days, and plateauing at around 20% after 1 year. Free pericardial fat grafts, harvested minimally invasively, demonstrated a promising retention rate after surgery, making them a suitable option for patients with a high risk of bronchopleural fistula.
Keywords: minimally invasive surgery; surgery; complications; thoracoscopy; VATS